Phytochemical, Proximate, Anti-Oxidant, and Anti-Inflammatory Properties of Aqueous and Methanol Extracts of Dried Shell of Cajanus cajan seed collected from a Rural Community in Nsukka, Enugu State, Nigeria - S. I. Orjiocha; M. U. Ibezim-Ezeani; F. C. Otuu; C. O. Ugorji (Journal of Applied Sciences and Environmental Management)
Cajanus cajan, commonly known as pigeon pea, is widely cultivated by farmers in Nsukka and other parts of Enugu State, Nigeria. The seeds have a long history of usage in the traditional food combinations of many families and are reportedly very nutritious. Hence, the objective of this paper is to investigate the phytochemical, proximate, anti-oxidant, and anti-inflammatory properties of aqueous and methanol extracts of the dried shell of Cajanus cajan seed collected from a rural community in Nsukka, Enugu State, Nigeria using appropriate standard techniques. Data obtained show that some of the analytical constituents were flavonoids (2,226.50 ± 47.350, Phenolics (6,294.65±117.35), Alkaloids (175.09±3.34), moisture (13.762%), ash (4.183%), and protein (9.01%). Some of the anti-oxidant properties - DPPH IC50 of 25.07 ± 0.09 µg/ml, nitric oxide scavenging activity equivalent to 20.0mM/g, and a Ferric Reduction Antioxidant Property (FRAP) value of 2.53 compared, favorably with ascorbic acid standard. The anti-inflammatory inhibition of the extracts was 44.1ug/mL as against standard diclofenac 37.62ug/mL. The extracts have promising properties as raw materials for developing anti-scaling agents for pipeline rust inhibition and nutriceuticals to manage oxidative stress-induced functional diseases.